(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The increasing request for space for private buildings was brought about by the utilization of the previous dumpsites. If the issue of leachate infiltration into the soil isn’t legitimately controlled it’ll lead to future harm in construction works. The objectives are to compare the geotechnical properties of soil of the contaminated and uncontaminated regions region of the dump site and evaluate if the effect of leachate on the geotechnical properties of soil changes with depth. Laboratory soil tests were conducted on the soil samples obtained and compared the effect of these leachates at the dump site. These methods are Natural water content, Bulk Density, Specific Gravity, Shear strength, and Consolidation tests. The soil samples were obtained from the contaminated region, and the uncontaminated region (i.e. at 100 m away from the dumpsite). All soil samples were obtained at depths 0.5m, 1.0m, and 1.5m below the ground level, to know the effect of leachate on the soil at the dumpsite and also to know if the effects of leachate changes with depth as it goes down the soil. The results obtained show that samples at 0.5m and 1m depth have been affected by leachates but the effects are not so significant at 1.5m depth, thereby making the soil at depths 0.5m and 1m unfit for construction purposes. This result was useful to check the land requirement in urban areas and guide the geotechnical engineers when designing and constructing foundations for buildings and other related structures on these types of soils.